Rancang Bangun Sistem Informasi Inventaris Gudang Menggunakan Metode Prototyping (Studi Kasus: UD. Rejeb Ngalah) - Fahmi Dwi Arianto Arianto; Evi Dwi Wahyuni; Wildan Suharso (Jurnal Repositor, 2023)
The CV. UD. Rejeb Ngalah is a company based in Nongkojajar. Rejeb Ngalah owns two SMEs that are developing and are kept for both SMEs. SMEs that are shaded by Rejeb Ngalah are Warnakarsa and Pesendaun located in Malang. This research is based on the researcher's desire to have and change for the better in society and to have a significant influence for better business processes than before. And we chose UD Rejeb Ngalah as a place of research because it had several problems experienced and it made the researchers intend to improve the processes in it. The main problem with Rejeb Ngalah is that between UKM Warnakarsa and Pesendaun, production and administrative activities are currently still carried out in different places and there are often misunderstandings among employees who handle administrative activities at Rejeb Ngalah because there is no warehouse information system for goods so that employees sometimes incorrectly inputting item data and causing the job-desk not to be properly organized as it should be. Because of the digital revolution, if a company wants to improve operations, it must develop new, more efficient business models [1]. Therefore, this research was conducted to develop an information storage system at UD. REJEB NGALAH to make it easier for employees to record goods, clarify the SOP of each employee and all administrative activities can be well organized. The research uses the prototyping method because it will be very effective if the client does not know what the website will actually be like. And at the wireframe/prototyping stage we can present what kind of website description is suitable for clients. The prototyping method can connect directly between developers and users with prototypes that have been designed before being implemented into coding so that the functionality of the system can be clearly described from the prototype [3]. It is certainly more effective for developers not to need to do coding before the user fits the system that has been described through the prototype.